Pengaruh Program Latihan Servis terhadap Pertandingan Siswa Ekstrakulikuler Bulutangkis di Sekolah Minu Bululawang - Akhmad Syahrul Muharram (LPPM Politeknik Pratama, 2024)
The short and long serve ability of badminton extracurricular students at the MINU Bululawang school is the background for this research. The game of one of the sports using a racket to hit a shuttlecock over the net is played by 2 people or four people in pairs who play against each other, also known as badminton. The point of this inquire about is to decide the impact of the benefit preparing program on competition among badminton extracurricular understudies at the MINU Bululawang School. Test investigate with a one bunch pretest-posttest plan was utilized in this investigate. The overall inquire about test comprised of 45 badminton extracurricular students. Serve blows are given for 4 weeks with a frequency of 4 times per week. The service training that has been given increases the results of short serves and long serves for badminton extracurricular students at the MINU Bululawang school with a sig level of 0.00 < 0.05.